The politicization of world politics and its effects: Eight propositions - Michael Zürn (European Political Science Review, 2014)
World politics is no longer a matter of executive multilateralism and technocratic expert decisions. What we see instead is the politicization of international institutions – a twofold process of growing resistance to and the more intensive utilization of these institutions. After providing evidence for this claim, this article develops propositions on the effects of politicization of world politics on the quality of decision making and the content of policies on both the international and national level. On the one hand, the politicization of international institutions arguably heralds a reflexive stage of global governance. The increased participation of societal actors leads to a new mode of decision making in world politics, which includes a notion of global common goods in conjunction with elements of public deliberation. By the same token, increased politicization of international institutions contradicts lamentations about the hollowing-out of national democracies and shows that political participation is in fact partly emigrating to the international level. While politicization has the inherent potential for initiating the democratization of international institutions and making new types of global policies possible, there are on the other hand several dangers associated to this process. First, it may perpetuate existing inequalities between North and South in terms of representation on the global level. Second, the politicization of world politics puts pressure on national democracy, since it moves attention away from national political matters and skews national policies towards universalist positions. Moreover, it arguably provokes the constitution of a new political cleavage, cosmopolitanism vs. communitarianism, which may possibly restructure politics in the 21st century to a large extent. These propositions on the effects of politicization will be developed with the help of empirical illustrations. However, they will not be systematically tested – the purpose of this contribution is to elaborate the analytical potential of a new concept and identify broad trends.
Keywords: 330; international institutions; democracy; domestic politics; cleavages